Manifestation of COVID-19 Mimicking Rheumatic Diseases : Review Article - Laniyati Hamijoyo; Angkasa Ramatuan Hamdan (Indonesian Rheumatology Association, 2020)
Background: Diagnosing the newfound disease has been always the vital strategy of controlling and managing Corona Virus Disease (COVID)-19. Interestingly, patients with COVID-19 may also have features mimicking rheumatic diseases due to immunology responses and viral properties. Objective: In this systematic review, we aim to highlight features of COVID-19 that mimic those of rheumatic diseases, in hope to raise clinical awareness and prevention. Methods: We systematically searched both from MEDLINE (accessed from PubMed) and Google scholar from late of 2019 to June 2020 for related published articles. In both electronic databases, the used key words were â€œCOVID-19â€ or â€œCorona virusâ€, â€œrheumatic diseasesâ€ and â€œclinical characteristicsâ€ Results: Through the search, we were able to conclude some characteristics that could be manifested both in COVID-19 infection and rheumatic diseases, including but not limited to constitutional manifestation, arthralgia and/or myalgia, myositis, hematologic manifestation, skin manifestation, acute interstitial pneumonia, myocarditis and gastrointestinal manifestation. Most studies were able to explain the possibility of immune dysregulation similar to what rheumatic diseases exhibit, include post mortem biopsy of a tissue damage similar to rheumatic complication in COVID-19 infection Conclusion: Since the possibility of overlap symptoms between COVID-19 infection and rheumatic diseases was able to be enucleated through our review, we believe that in the future clinical awareness to differentiate between autoimmune and infection origin of many rheumatic manifestations will hold pivotal role in prohibiting reemergence disease. Future study to assist clinicians to swiftly diagnose autoimmune diseases in the era of pandemic is essential.